2013
DOI: 10.1111/1742-6723.12097
|View full text |Cite
|
Sign up to set email alerts
|

2010–2011 Queensland floods: Using Haddon's Matrix to define and categorise public safety strategies

Abstract: The present study and its integration of research findings and conceptual frameworks might assist governments and communities to develop policies and strategies to prevent flood injury and fatalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 20 publications
(53 reference statements)
0
33
0
Order By: Relevance
“…According to the Australian Bureau of Transport Economics, flood has been the most costly disaster type in Australia, followed by severe storms and cyclones [51]. However, data on human health impacts of floods can be difficult to source, although a study has shown that heavy rainfall and consequent extensive flooding in Queensland in 2010–2011 attributed to 33 deaths [52]. The Insurance Council of Australia provides cost estimates of natural disasters such as death and injuries by hazard type [51], and these could be a potential source of data on injuries and mortality from extreme weather events.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Australian Bureau of Transport Economics, flood has been the most costly disaster type in Australia, followed by severe storms and cyclones [51]. However, data on human health impacts of floods can be difficult to source, although a study has shown that heavy rainfall and consequent extensive flooding in Queensland in 2010–2011 attributed to 33 deaths [52]. The Insurance Council of Australia provides cost estimates of natural disasters such as death and injuries by hazard type [51], and these could be a potential source of data on injuries and mortality from extreme weather events.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we propose to explore the suitability of publicly available census data to be considered as proxies for behavioral response in flash flood circumstances. In general, findings from flash flood or flood human‐impact studies were cross‐checked with arguments from the literature on social vulnerability to flooding and natural hazards in general . The indicators quantifying vulnerability and the prominent human risk during flash floods are considered according to the following criteria: The temporal phase of the event: Some indicators can be indicative of vulnerability in the preparation or the recovery but not in the emergency phase of the hazard .…”
Section: Data Sets and Methodsmentioning
confidence: 99%
“…The indicators quantifying vulnerability and the prominent human risk during flash floods are considered according to the following criteria: The temporal phase of the event: Some indicators can be indicative of vulnerability in the preparation or the recovery but not in the emergency phase of the hazard . For example, flood insurance cannot directly reduce vulnerability during flooding but may facilitate the recovery process after a flood disaster . As another example, gender is used as a proxy with different meanings depending on the stage of a disaster.…”
Section: Data Sets and Methodsmentioning
confidence: 99%
“…The immediate health impacts described in the literature were predominantly non-communicable and included deaths, 3 injuries [3][4][5][6][7][8] and physiological distress; 3,5 infectious diseases 3,5,9 were also a potential risk. Injuries requiring medical attention can occur shortly before a flood (e.g., during evacuation), and during and after the event (e.g., drowning, 3,10 musculoskeletal stress, 7 punctures and lacerations, 4,8 electrocution 3 and carbon monoxide poisoning 6,7 ).…”
mentioning
confidence: 99%